2014
DOI: 10.1002/hed.23462
|View full text |Cite
|
Sign up to set email alerts
|

Examining tumor control and toxicity after stereotactic body radiotherapy in locally recurrent previously irradiated head and neck cancers: Implications of treatment duration and tumor volume

Abstract: SBRT ± cetuximab achieves promising tumor control and survival with low rates of acute/late toxicity even for recurrences >25 cc. Prolongations in treatment time may decrease late toxicity at the expense of disease control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 22 publications
4
52
2
Order By: Relevance
“…Earlier reports from the SBRT literature have reported higher rates of carotid blowout syndrome (26,27) not seen in our experience or in the French experience (21,28). This may relate in part to differences in fractionation schema where SBRT was delivered every other day rather than every day (29,30). Although the protocol did not specifically exclude patients or handle the carotid differently, larger retrospective series have examined clinical factors that may help in future patient selection to lower the potential risk of this often-fatal complication (31).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Earlier reports from the SBRT literature have reported higher rates of carotid blowout syndrome (26,27) not seen in our experience or in the French experience (21,28). This may relate in part to differences in fractionation schema where SBRT was delivered every other day rather than every day (29,30). Although the protocol did not specifically exclude patients or handle the carotid differently, larger retrospective series have examined clinical factors that may help in future patient selection to lower the potential risk of this often-fatal complication (31).…”
Section: Discussioncontrasting
confidence: 72%
“…Although the protocol did not specifically exclude patients or handle the carotid differently, larger retrospective series have examined clinical factors that may help in future patient selection to lower the potential risk of this often-fatal complication (31). Nonetheless this prospective phase 2 study with uniform patient selection and SBRT plus cetuximab dose confirms the safety seen in more heterogeneous primarily retrospective data sets subject to inherent biases of retrospective design (30); similar to the results seen in the locally advanced and metastatic setting, the combination of cetuximab and SBRT appears safe in the reirradiation of rSCCHN, and may improve outcomes (14,15). The safety and potential efficacy of SBRT and cetuximab transcended treatment platform with no significant differences observed in outcome, toxicity, or feasibility between the examined SBRT modalities (Cyberknife, Trilogy, or TrueBeam).…”
Section: Discussionsupporting
confidence: 56%
“…40 In addition, larger treatment volumes have been associated with increased toxicity. Vargo et al 52,53 reported that GTV >25 cm 3 was associated with increased acute toxicity among patients receiving SBRT reirradiation. Two other studies on IMRT and proton reirradiation reported that a clinical target volume (CTV) 50 cm 3 was a predictor for increased toxicity.…”
Section: Tumor Volumementioning
confidence: 99%
“…[57][58][59] In a matched case-control study on SBRT reirradiation, Heron et al 46 reported a locoregional control and OS benefit with concurrent cetuximab over reirradiation alone. 53 51,52 However, in retrospective studies, including patients treated with and without concurrent chemotherapy, concurrent chemotherapy was found to be associated with increased serious toxicity, in both IMRT studies 11,12 and SBRT studies.…”
Section: Concurrent Systemic Therapymentioning
confidence: 99%
“…SBRT techniques for target delineation, patient setup, and treatment/delivery have been previously described 7,8,10,11 Briefly, SBRT planning was CT-based or PET/CT-based with custom thermoplastic mask for immobilization delivered using one of several treatment platforms including Cyberknife™ (Accuracy, Inc., Sunnyvale, CA), Trilogy™, and TrueBeam™ (Varian Medical Systems Inc., Palo Alto, CA). SBRT consisted of 40-50Gy in 5 fractions depending on treatment volume ≥25cc, delivered on alternating days over 1-2 weeks.…”
Section: Methodsmentioning
confidence: 99%